Orientações curriculares para o ensino de português para surdos: análise de documento do município de São Paulo - Cruz, Márcia (Universidade Federal de São Carlos, 2019)
The education of deaf people has been a frequent theme in recent years, due to laws and decrees aimed at ensuring bilingual education. The teaching of the Portuguese language as a second language stands out as one of the most controversial aspects, because in the present time there is no curriculum designed for this public.. Faced with this fact, the material "Curriculum Guidelines and Proposition of Learning Expectations for Early Childhood Education and Elementary Education: Portuguese Language for Deaf People" is of great relevance, due to its teaching proposal to deaf students and its pioneering in the city from São Paulo. The objective of this qualitative and documental study was to investigate the concepts of deaf subjects, bilingual education and Portuguese language teaching for deaf people present in this material, considering the moment in which it was produced, the current legislation, and the conceptions adopted by the city. The three conceptions cited included the analysis categories of this dissertation. The concepts present in the document were analyzed and discussed from the current legislation and based on renowned area's authors. The recognition of deafness as a linguistic difference was identified, the Libras as the first language and Portuguese as the second language, inferring simultaneous bilingualism. The results demonstrate the importance of sign language to deaf children, as well as proposals and methods to teach Portuguese language, from the development of different textual types for each year, meeting the needs of students and teaching as second language. As a conclusion, it was identified that the politics of the city of São Paulo shows respect to the deaf subject and his form of expression, indicating Libras and Portuguese Language in an equitable way; the document shows new perspectives for the teaching of Portuguese for the deaf student. Despite some shortcomings, the document meets its objectives, proving to be advanced to the moment in which it was elaborated and with potential of use and application still in the present moment.
Curricular guidelines for portuguese education for deaf: analysis of document of the municipality of São Paulo
Keywords: Português como segunda língua; Educação de surdos; Bilinguismo; Surdez; Educação Especial; Portuguese as a second language; Education of the deaf; Bilingualism; Deafness; Special education; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL